Cervical Pessary versus Expectant Management for the Prevention of Delivery Prior to 36 Weeks in Women with Placenta Previa: A Randomized Controlled Trial - Stafford, Irene A.; Garite, Thomas J.; Maurel, Kimberly; Combs, C. Andrew; Heyborne, Kent; Porreco, Richard; Nageotte, Michael; Baker, Susan; Gopalani, Sameer; Dola, Chi; How, Helen; Das, Anita F.; the Obstetrix Collaborative Research Network (American Journal of Perinatology Reports, 2019)
Objective This multicenter randomized controlled trial compared cervical pessary (CP) versus expectant management (EM) in women with placenta previa between 22.0 and 32.0 in prolonging gestation until ≥ 36.0 weeks' gestation.Study Design This study took place from November 2016 to June 2018. Women were randomized to receive either the Bioteque CP or EM. The pessary was removed at ≥ 36.0 weeks unless indicated. The primary outcome was gestational age (GA) at delivery, with secondary outcomes including need for transfusion, number and duration of antepartum admissions, type of delivery, and neonatal outcomes. A total of 140 patients were needed to show a 3-week prolongation of pregnancy in the pessary group; however, the trial was stopped early due to budgetary issues.Results Of the 33 eligible women, 17 were enrolled. Although not statistically significant, the mean GA at delivery in the CP group was greater than women in the EM group (36.5 ± 1.23 vs. 36.0 ± 2.0; p = 0.1673). The number and duration of antepartum admissions was greater in the EM group (2.7 ± 0.58 vs. 16.0 ± 22.76 days; p = 0.1264) as well.Conclusion Although the study was underpowered to determine the primary outcome, safety and feasibility of CP in pregnancies complicated with previa were demonstrated.
Keywords: placenta previa; pessary; hemorrhage; preterm birth